Selection and Performance Evaluation Process for Indonesian Hajj Officials at the Directorate General of Hajj and Umrah, Ministry of Religious Affairs of the Republic of Indonesia - Aulia Kania Rifatama Garini; Nidya Dudija (International Journal of Science and Environment (IJSE), 2025)
This study aims to analyze the selection and performance evaluation strategies of Indonesian Hajj officers by the Directorate General of Hajj and Umrah of the Ministry of Religious Affairs of the Republic of Indonesia. The selection process is carried out through administrative stages, computer-based tests (CAT), and panel interviews. Performance evaluation is carried out from the training stage to the implementation of tasks in Saudi Arabia through direct supervision and daily reporting. This study uses a descriptive qualitative approach with interviews, documentation, and participatory observation. The results indicate that the success of selection and evaluation is determined by system integration, individual competence, and institutional support. However, there are still challenges such as disparities in training quality between regions, limitations in the digital system, and the absence of standardized and measurable performance indicators. This study recommends the development of national competency standards, strengthening the performance management information system, and the implementation of Balanced Scorecard-based indicators. This study is expected to provide strategic input for policymakers in improving the quality of Hajj services and enriching academic literature on human resource management in the religious sector.